Nepravilnosti pri izplačilih plač v državnih organih in občinah, kot jih ugotavlja Računsko sodišče - Zemljič, Petra (Delavci in delodajalci, 2009)
The author presents irregular practices of the public authorities and municipalities regarding to payments of wages and other rights in the field of public service labour relations, as reviewed by the Court of Audit of the Republic of Slovenia.
Keywords: delovna razmerja; javna uprava; javni uslužbenci; plače; zaposleni